Cooking for food scientists - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Food processing technology. Principles and practice P J Fellows, 2nd edition. Woodhead Publishing. 2000. 656 pp. ISBN 1 85573 533 4 GBP 35 E 52.50 Woodhead Publishing Abington Hall, Abington Cambridge CB1 6AH England Fax: +44 12 23 89 36 94